A 16-week progressive exercise training intervention in treatment-naïve chronic lymphocytic leukaemia: a randomised-controlled pilot study - Brown, Frankie F.; Oliver, Rebecca; Eddy, Rachel; Causer, Adam J.; Emery, Annabelle; Collier-Bain, Harrison D.; Dutton, David; Crowe, Josephine; Augustine, Daniel; Graby, John; Rees, Daniel; Rothschild-Rodriguez, Daniela; et al. (Frontiers in Oncology, 2024)
BackgroundChronic lymphocytic leukaemia (CLL) typically presents with asymptomatic, early-stage disease that is monitored until disease progression (‘treatment-naïve’ CLL). The objective of this pilot study was to assess the feasibility and preliminary safety of an exercise program in treatment-naïve CLL. We also sought to preliminarily assess the impact of the exercise program on disease activity, as it has been proposed that exercise training may reduce disease outgrowth in treatment-naïve CLL.MethodsA total of 40 treatment-naïve CLL patients were recruited into this randomised-controlled pilot study, and after screening, n = 28 were randomised into a 16-week, home-based, partially supervised, personalised, progressive exercise intervention (n = 14: mean ± SD: age = 62 ± 12 years) or 16 weeks of usual care, control group (n = 14: mean ± SD: age = 61 ± 10 years). The primary outcome measures were safety (number and severity of adverse events) and feasibility (uptake, retention, and adherence to the trial). Disease activity (CD5+/CD19+ CLL cells clonally restricted to kappa or lambda) and other immune cell phenotypes, with a principal focus on T cells, were measured by flow cytometry. Other secondary outcomes included DEXA-derived body composition, cardiorespiratory and functional fitness, resting cardiovascular measures.ResultsTrial uptake was 40%, and the overall retention rate was 86%, with 79% of the exercise group and 93% of the control group completing the trial. Adherence to the exercise intervention was 92 ± 8%. One serious adverse event was reported unrelated to the trial, and one adverse event related to the trial was reported. The exercise intervention elicited a 2% increase in DEXA-derived lean mass in the exercise group compared with a 0.4% decrease in the control group (p = 0.01). No between-group differences were observed over time for whole-body mass, BMI, bone mineral density, body fat, blood pressure resting heart rate, or measures of cardiorespiratory or functional fitness (all p > 0.05). No between-group differences were observed over time for clonal CLL cells and CD4+ or CD8+ T-cell subsets (all p > 0.05).ConclusionThe exercise training program used in this study was feasible in people with treatment-naïve CLL who passed pre-trial screening, and we preliminarily conclude that the exercise training program was safe and also resulted in an increase in lean mass.Clinical trial registrationhttps://doi.org/10.1186/ISRCTN55166064, identifier ISRCTN 55166064.